Consumer awareness towards products of Sime Darby Foods and Beverages Marketing Sdn Bhd / Farrah Mastura Mat Jan - Mat Jan, Farrah Mastura (Faculty of Business and Management, 2011)
The increase of a new product’s sales is usually attributed to consumers becoming informed about the existence of the product. Promotional tools can accelerate this consumer awareness process. This paper evaluate this effect; the effect of media advertising, sales promotion and word-of-mouth towards the awareness among consumers of Sime Darby Foods and Beverages Marketing Sdn Bhd (SDFBM). This descriptive study is to describe the awareness of consumers towards Sime Darby Foods brand name. The sample consisted of 50 shoppers at Cold Storage Supermarket in Subang Parade. Reliability test, Descriptive analyses and Correlation test were used to evaluate the relationship of the three promotional tools used by the company towards the awareness of the consumers. The findings showed that there were low effects between sales promotions done by the company towards consumers’ awareness. As for the other two promotional tools, the effects to consumer’s awareness were very low. Based on the findings, the awareness among consumers towards products of Sime Darby Foods and Beverages Marketing can be descript as low and the advertising and promotional campaign done by the company was not giving significant impact to the consumers to becoming informed about the company foods and beverages products. For marketers of fast moving consumer goods, especially foods and beverages, it is important to note that there is a need to continuously monitor the impact of the advertising and promotional activities that had been carried so far, so that correction and improvement can be planned to achieve a higher awareness among the consumers.